A 3D triple-deck photoanode with a strengthened structure integrality: enhanced photoelectrochemical water oxidation. Issue 6 (22nd January 2016) - Ma, Ming; Shi, Xinjian; Zhang, Kan; Kwon, Soonwoo; Li, Ping; Kim, Jung Kyu; Phu, Thanh Tran; Yi, Gi-Ra; Park, Jong Hyeok
Abstract : The optimal utilization of interfaces between every layer in a triple-deck 3D architecture realizes enhanced water oxidation efficiency. Abstract : WO3 /BiVO4 is one of the attractive Type II heterojunctions for photoelectrochemical (PEC) water splitting due to its well-matched band edge positions and visible light harvesting abilities. However, two light absorption components generally suffer from poor charge collection and cannot be efficiently utilized because of non-ideal interfaces. Herein, a triple-deck three-dimensional (3D) architecture was designed through a one-step shaping process with an additional stress relaxation WO3 underlayer. The final photoanodes showed a promising photocurrent density of 5.1 mA cm −2 at 1.23 V vs. RHE under AM 1.5G illumination. Using the uniformly distributed oxygen evolution co-catalyst (OEC) layer as the outer most shell of the WO3 /BiVO4 /OEC triple-deck 3D structure with a dense WO3 underlayer, the water splitting efficiency was improved dramatically by facilitating the charge transfer process at the electrode/electrolyte interface.